Alternative Learning Methods Employed by Language Teachers in the New Normal of COVID-19 - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; Anak Agung Istri Yudhi Pramawati (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTLearning activities should be conducted effectively to create conducive learning conditions to develop students’ creativity and their higher learning competence. Through conducting appropriate and effective learning activities, the learning objectives and learning competencies are easier to achieve. To create effective learning activities, teachers are required to have adequate understanding and competence in employing learning methods. This study aims to explore effective learning methods to create more creative learning activities for the students. This study found several alternative learning methods that can be utilized in the time of the new normal of covid-19 to continually improve the students’ competence. This study implies that teachers should continually expose themselves to various learning methods to establish conducive learning conditions in the classroom. ABSTRAKKegiatan pembelajaran harus dilakukan secara efektif untuk menciptakan kondisi pembelajaran yang kondusif untuk mengembangkan kreativitas dan kompetensi belajar siswa yang lebih tinggi. Melalui pelaksanaan kegiatan pembelajaran yang tepat dan efektif, tujuan pembelajaran dan kompetensi pembelajaran lebih mudah dicapai. Untuk menciptakan kegiatan pembelajaran yang efektif, guru dituntut memiliki pemahaman dan kompetensi yang memadai dalam menggunakan metode pembelajaran. Penelitian ini bertujuan untuk menggali metode pembelajaran yang efektif untuk menciptakan kegiatan belajar yang lebih kreatif bagi siswa. Penelitian ini menemukan beberapa metode pembelajaran alternatif yang dapat dimanfaatkan pada masa new normal covid-19 untuk terus meningkatkan kompetensi siswa. Studi ini menyiratkan bahwa guru harus terus-menerus mengekspos diri mereka kedalam berbagai metode pembelajaran untuk membangun kondisi pembelajaran yang kondusif di dalam kelas.